Structural properties and static robustness of Linux software network - Ershen WANG; Yu LI; Chen HONG; Qinghua SUN; Chang LIU (Dianxin kexue)
The source code of the Linux software was analyzed,and the directed function call network model,the weak coupling network model of software system,the strong coupling network model and the strong connected subgraph model were built.The characteristics and static robustness of the four networks were studied.The results show that four networks all show ‘small-world’ property.The out-degree distribution of the six modules in the Linux network generally follows the exponential distribution,and the in-degree distribution of the six modules follows the power law.The best attacking strategy was distinct when different robustness evaluation indicator was adopted.For the weak connectivity indicator,high in-degree attacking strategy was of the greatest damage to the weakly coupled software network.